The Familiar Made Strange : American Icons and Artifacts after the Transnational Turn - DeLay, Brian, 1971-; Bradley, Mark, 1961-; Blower, Brooke Lindy, 1976- (Book collections on Project MUSE., 2015)
In The Familiar Made Strange, twelve distinguished historians offer original and playful readings of American icons and artifacts that cut across rather than stop at the nation's borders to model new interpretive approaches to studying United States history. These leading practitioners of the "transnational turn" pause to consider such famous icons as John Singleton Copley's painting Watson and the Shark, Albert Eisenstaedt's photograph V-J Day, 1945, Times Square, and Alfred Kinsey's reports on sexual behavior, as well as more surprising but revealing artifacts like Josephine Baker's banana skirt and William Howard Taft's underpants. Together, they present a road map to the varying scales, angles and methods of transnational analysis that shed light on American politics, empire, gender, and the operation of power in everyday life. Contributors: Brooke L. Blower, Boston University; Mark Philip Bradley, University of Chicago; Nick Cullather, Indiana University; Brian DeLay, University of California-Berkeley; Matthew Pratt Guterl, Brown University; Jesse Hoffnung-Garskof, University of Michigan-Ann Arbor; Fredrik Logevall, Cornell University; Mary A. Renda, Mount Holyoke College; Daniel T. Rodgers, Princeton University; Andrew J. Rotter, Colgate University; Brian Rouleau, Texas A & M University; Naoko Shibusawa, Brown University